Islam, Local Culture, and Japan-Indonesian Relations - Muhammad Nida' Fadlan; Dadi Darmadi (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2014)
Local culture is undoubtedly a very important aspect to every nation. Having an awareness of local culture, especially among the youth, plays a great role in shaping a society and a state. For one to have an appreciation of another country’s culture, however, can be an important starting point in breaking down barriers of misperceptions or misunderstandings, and in helping to build global relationships. In support of this idea, the Japanese Embassy in Jakarta this year offered a special program called the Japan-East Asia Network of Exchange for Students and Youth (JENESYS) to strengthen the awareness of Japanese local culture among Muslim youth in Indonesia. In early 2014, the Japanese government, working in cooperation with PPIM (Center for the Study of Islam and Society) at UIN Syarif Hidayatullah in Jakarta, invited a number of university students to visit Japan.DOI: 10.15408/sdi.v21i2.1044